The Relationship Between The Rationality Of Prescribing And The Quality Of Life Of Hypertension Patients At The Central Siantan Health Center In Pontianak - Muhammad Akib Yuswar (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Hypertension is a silent killer disease that can affect the patient's quality of life. There is a need for rational treatment to achieve the success of therapy and the desired quality of life. This study aims to determine the relationship between the rationality of prescribing and the quality of life of hypertensive patients. The study design was an observational cohort. Data were obtained from hypertensive patients at the Puskesmas Siantan Tengah Pontianak who met the inclusion criteria in June-July 2021 using a prospective purposive sampling and collected from medical records, EQ5D5L and VAS questionnaires. The results of the study on 101 samples were obtained; the rationality of prescribing antihypertensive drugs was rational, with the percentage of rationality being the appropriate indication 87,12%; appropriate drug 87.12%; appropriate patient 88.11%; and appropriate dose 88.11%. In addition, 28 patients (27.72%) did not have a problem with the five dimensions with the highest EQ5D5L index of 1,000, while the quality of life, as measured by VAS, had a median value of 60. The results of the Pearson chi-square test showed that there was a relationship between the rationality of prescription and quality of life for hypertensive patients with a significance value ≥ 0.05 using the EQ5D5L (p = 0.688) and VAS (p = 0.583) questionnaires. Conclusion: there is no significant relationship between the rationality of prescribing and the quality of life of hypertensive patients, both using the EQ5D5L and VAS questionnaires.